Gatekeeping the Plenary Floor: Discourse Network Analysis as a Novel Approach to Party Control - Bhattacharya, Caroline (2020)
In the German parliament, the Bundestag, floor time is a scarce resource and is allocated to MPs by leaders of their respective parliamentary party groups. Previous research indicates that highly salient plenary debates tend to be dominated by party leaders and other loyal frontbenchers. Plenary speeches can therefore offer only limited insights into party unity. Any MP can give a so-called ‘explanation of vote’ (EoVs) to justify their voting decision and/or express their point of view. These written statements provide a more accurate depiction of the range of viewpoints present within legislative parties. In order to assess the effect of party control on observed party unity and parliamentary contestation, discourse network analysis has been employed in this study to compare legislative speech with EoVs in debates on the Greek crisis between 2010 and 2015. Discourse network analysis combines content analysis with an actor-centred approach, and this is the first time this method has been used to study party control and (dis)unity. Bundestag debates on the Greek crisis present an interesting case study, as the issue became increasingly controversial over time, both in the public and the legislature. While this became evident in declining voting unity and individual-level mobilisation through EoVs, the extent to which gatekeeping impedes contestation on the plenary floor needs to be assessed. In terms of representation, it is important that European Union issues not only make it to the plenary agenda but that these debates also reflect the different viewpoints of MPs.